Experimental Study on Uniaxial Compression Fracture Process of Marble Specimens with Circular Holes with Different Diameters - Peng Yan-yan; Xing Ming-hong; Lin Qun-chao; Guo Peng-fei (Geofluids)
After a long period of geological tectonic action, the rock mass develops defects such as pores and fissures of different sizes and scales. The mechanical properties of the rock are largely affected by these discontinuous structures, and there will be obvious stress concentration at the edge of the hole inside the rock. Under the action of concentrated stress, cracks initiate, expand, and penetrate from the edge of the hole to form the final fracture surface and cause instability and failure of the rock mass. In practical engineering, due to the limitation of various factors, it is impossible to conduct uniaxial compressive strength test for each geotechnical engineering. Therefore, the rock in the weak part of the project can be selected as the test specimen before the indoor physical tests. In this paper, the static uniaxial compression test of specimens with circular holes with different diameters is carried out. Digital Image Correlation (DIC) monitoring system is used to observe the test process in real time; then, the data from uniaxial compression test and DIC monitoring test are obtained. At the same time, the macroscopic failure characteristics and crack propagation law of rock specimens are obtained, and the evolution law of strain field during the failure process of rock specimens is also obtained. Meanwhile, Realistic Failure Process Analysis (RFPA) is carried out to verify the accuracy of static uniaxial compression physical tests numerically. Physical tests show that the uniaxial compressive strength of marble specimens with circular holes and the dispersion of measured peak stress data decrease with the increase of hole diameter. The main failure type of marble specimens with circular holes is tension shear failure; the macroscopic failure zone of the sample, the strain field localization zone, and the maximum shear stress field of the numerical test are distributed in a semi-“X” shape with the hole as the center. The localization zone of the strain field on the specimen is usually the region of crack initiation, propagation, and penetration on the surface of the marble specimens. It also shows that specimen breaks in the radial direction along the y-axis of the circular hole, and cracks connecting both ends of the circular hole and the specimen are generated on the specimen. It is of great theoretical value and practical significance to the influence of the cavities in the rock specimens on the stress and strain characteristics and the initiation, propagation, and penetration modes.